Building the army's backbone Canadian non-commissioned officers in the Second World War - Brown, Andrew L. 1968- (UBC Press, 2022)
"In September 1939, the Canadian army, a tiny force of around 55,000 regulars and reservists, began a remarkable expansion. "Building the Army's Backbone" tells the story of how senior leadership created a corps of non-commissioned officers (NCOs) that helped the burgeoning force train, fight, and win. This innovative book uncovers the army's two-track NCO production system: locally organized training programs were run by units and formations, while centralized programs were overseen by the army. Ultimately, this two-pronged system produced a corps of NCOs that collectively possessed skills in leadership, tactics, and instruction to help the army succeed in battle."--
Keywords: Kanada -- Canadian Army; Geschichte; Zweiter Weltkrieg; Unteroffizier; Canada / Canadian Army / Non-commissioned officers / History / 20th century; Canada / Canadian Army / Non-commissioned officers / Training of / History / 20th century; Canada / Canadian Army / Non-commissioned officers / Recruiting, enlistment, etc / History / 20th century; World War, 1939-1945 / Canada; HISTORY / Military / Canada; Canada / Canadian Army; Armed Forces / Non-commissioned officers; Armed Forces / Non-commissioned officers / Training of; Canada; 1900-1999; History